Biochemical composition and caloric value of pelagic fsh and squids from the Okhotsk Sea - K. M. Gorbatenko; I. V. Melnikov; E. E. Ovsyannikov; S. L. Ovsyannikova (Известия ТИНРО, 2018)
Main bioenergetic parameters are evaluated for 14 species of pelagic fsh and squids from the Okhotsk Sea, with special attention to walleye pollock and pacifc herring. Caloric value of the muscle tissues varies from 867 cal.g–1 (squid) to 2062 cal.g–1 (chinook salmon) in wet weight and from 5151 to 6484 cal/g in dry weight. The studied nekton species are mostly distinguished by high caloric value of the muscle tissue, with exception for pollock and squids with the value < 1000 cal/g WW. Lipid fraction in the pollock tissues varies from 0.7 to 1.1 %, proteins are 15.5–17.9 %, and carbohydrates — 0.6–0.7 % in wet weight, the average caloric value is 979–1131 cal.g–1 WW or 5154–5264 cal.g–1 DW. Dynamics of the main biochemical parameters and the total caloric value shows weak ontogenetic changes for the pollock muscles, without signifcant difference between different stages of gonad maturity both for males and females. During maturation, amount of accumulated energy remains constant in soma, but changes in liver and gonads of pollock, and their energy content is noticeably higher for females than for males: on average in 3 times in gonads and in 1.5 times in liver. The total amount of energy accumulated by pollock during its life cycle from juvenile (< 17 cm) to extra large individuals (> 60 cm) is estimated as 1964 kcal for females and 1465 kcal for males. Caloric value for the muscle tissue of mature herring is lower in spring (on average 1498 cal.g–1 WW) than in autumn (1676 cal.g–1 WW), and for the whole body (mince) is in 1.2 times higher for juveniles, in 1.7–1.8 times higher for adults in spring, and in 2.1–2.2 times higher for adults in autumn after fattening, with average exceeding in 20–40 %. Lipid fraction in the herring tissues is on average 6.2 % in spring and 6.6 % in autumn. In spring, the maximum values of biochemical parameters are registered for the herring with gonad maturity at stage III. Later, during transition to the stage IV, and especially to the stage V, the fat decreasing and proteins watering is observed in its muscles. On opposite, the post-spawning herring at stage VI–II has the minimum parameters and caloric value in spring but enhances them to autumn, after intensive fattening, when caloric value of its mince becomes twice higher than for muscle tissue because of lipids accumulation in the subcutaneous tissue. The main energy parameters of the mature herring tissues in autumn are close to those in spring (by maturity stages), with only slight increase of fatness and caloric value, which are the maximum in autumn for mince, mostly because of fat accumulation in viscera and subcutaneous tissue. Caloric value of the herring gonads varies from 1330 to 1714 cal.g–1 WW, 4809–5894 cal.g–1 DW for females and from 1155 to 1604 cal.g–1 WW, 4809–5894 cal.g–1 DW for males, with the maximum at the maturity stage IV (the same as fat content), both for males and females. The gonads caloric value is higher in spring, immediately before spawning. For herring, the major amount of energy is concentrated in soma, and its portion increases during the life cycle from 55.0 to 72.1 %, on average. Males and females of herring have common patterns of this value dynamics in the process of ontogenesis, though females have higher percentage for gonads. In annual cycle, the maximum portion of energy concentrates in the herring gonads in spring (16.7–22.1 % for females and 13.1 % for males) and decreases to autumn. The total amount of energy accumulated by herring during its life cycle is estimated as 542 kcal for females and 476 kcal for males. Females accumulate more because the oogenesis requires more energy than spermatogenesis.